The impact of stringent insider trading laws and institutional quality on cost of capital - Kwabi, Frank O.; Boateng, Agyenim; Adegbite, Emmanuel (Elsevier, 2018)
This paper examines the effects of interaction between stringent insider trading laws, institutional quality and equity portfolio allocation on the cost of capital. Using a dataset drawn from 44 countries over the period from 2001 to 2015, we find that stringent insider trading laws interact with institutional quality and foreign equity portfolio allocation to reduce the country-level cost of capital. Further analysis from a quasi-natural experiment based on the 2008–2009 global financial crisis suggests that the findings are robust to endogeneity. Our results imply that the enactment of stringent insider trading laws and their interplay with the quality of institutions are not only important to portfolio investment allocation decisions but reduce the country-level cost of capital.